Faktor-faktor pendukung dan penghambat dalam penerapan manajemen data penelitian (research data management) di lembaga penelitian - Ari Zuntriana (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2020)
Research data management has not been widely implemented In Indonesia. However, several research institutions have successfully adopted it with various levels of implementation. Various obstacles faced by research institutions and universities may cause the slow implementation of RDM. Nevertheless, institutions that have implemented RDM also have supporting factors that potentially help in accelerating RDM implementation. To find out the factors that support and hinder the RDM implementation in research organizations, the researcher conducted a study of two research institutions, namely CIFOR and LIPI. This research was a qualitative study and the data were collected through direct interviews. The results of the interviews were then processed and analyzed using the thematic analysis method. The results of the study show that the two institutions have several supporting factors in carrying out RDM, namely: the character of the organization which is a research institution, the involvement of overall management in the advocacy process, the existence of supporting policies, and the existence of outreach and training activities for the researchers. Meanwhile, the hindering factors are the researchers who have not been familiar with RDM, the resignation of some researchers at CIFOR, and the uneven competence of human resources in PDDI LIPI. The last two inhibiting factors are uniquely experienced by respective institutions. The successful implementation of RDM in research institutions requires the cooperation of all parties at all levels of management. In addition, research organizations need to provide support services, namely research data services, data literacy training for researchers and librarians, and the availability of institutional policies.